COVID-19 and Obesity: When an Epidemic meets a Pandemic - Paracha, Anousheh Awais (Journal of the Pakistan Medical Association, 2021)
Obesity has emerged as an epidemic worldwide, with an incidence of more than 40% in the United States and Europe. (2)The results of this study raise major concerns for Pakistan, where food is a major part of the culture. A healthy diet is often misunderstood as the consumption of desi ghee, sweets, and fatty foods.(3) The fast-food industry is growing rapidly in Pakistan, leading to greater consumption of foods rich in cholesterol and saturated fatty acids. According to a study by Pellegrini et al., lockdown has contributed to reduced exercise, anxiety, boredom, and unhealthy eating habits.(4) A higher percentage of body fat has increased the risk of multimorbidity which is considered as a risk factor of COVID-19.(5) A thorough online literature search was carried out on PubMed, and PakMediNet and no research was found assessing the correlation between obesity and COVID-19 in Pakistan. This shows the lack of attention given to this factor in the country. It is the duty of the physician to educate patients about the possible risks associated with obesity. This should be done keeping in view the patients’ socio-economic background, ensuring that the treatment plan is economically feasible. Patients should be advised to follow a balanced diet including vegetables and organic foods while avoiding junk food and frequent visits to restaurants. Adults and children should follow an active lifestyle where emphasis must be placed on daily exercise, a healthy breakfast, and a proper sleep schedule. It is imperative that patients are aware of the multimorbidity associated with obesity to lessen the burden on the health facilities in Pakistan and promote patient health. Continuous...